Silicon dioxide aerogel slurry as well as preparation method and application thereof

By using a ternary composite system of anionic surfactants, polymer electrolytes and suspending agents in silica aerogels, combined with stirring and vacuum degassing processes, the interface of silica aerogels in aqueous systems is solved. Problems with poor compatibility and bubbles are achieved, and a stably dispersed and bubble-free slurry is achieved, improving its application performance in building materials.

CN119350893APending Publication Date: 2025-01-24BEIJING NEW BUILDING MATERIALS PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The poor interfacial compatibility of silica aerogel in aqueous systems leads to difficult stability and bubble problems in its application in building materials, affecting product quality.

Method used

A ternary composite system of anionic surfactant, polymer electrolyte and suspending agent is used to prepare a stably dispersed and bubble-free silica airgel slurry through stirring and vacuum degassing processes.

Benefits of technology

The stable dispersion and bubble-free characteristics of the silica airgel slurry are achieved, and its application performance and product quality in building materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087538730000051
    Figure BDA0005087538730000051
  • Figure BDA0005087538730000061
    Figure BDA0005087538730000061
  • Figure BDA0005087538730000062
    Figure BDA0005087538730000062
Patent Text Reader

Abstract

The invention provides silicon dioxide aerogel slurry as well as a preparation method and application thereof. The silicon dioxide aerogel slurry is prepared from the following materials in parts by weight: 10 to 90 parts of water, 1 to 25 parts of silicon dioxide aerogel powder, 0.01 to 3 parts of an anionic surfactant, 0.01 to 0.9 part of a polymer electrolyte, 0.01 to 1 part of a suspending agent, 0.001 to 0.01 part of a pH (Potential of Hydrogen) regulator, 0.001 to 0.02 part of a de-foaming agent and 0.001 to 0.01 part of a sterilizing agent. The dosage of the adopted additive is small, the influence on the structure and performance of the aerogel is reduced, and the prepared aerogel slurry still keeps high hydrophobicity and low thermal conductivity after being dried.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a silicon dioxide aerogel slurry and a preparation method and application thereof. Background Art

[0002] Aerogel is a porous material composed of a three-dimensional nanoparticle skeleton and nanoscale pores. It has the characteristics of low density, high porosity, high specific surface area, low thermal conductivity and strong fire resistance. It has brought new development opportunities for traditional thermal insulation materials and also provided a possibility to solve the contradiction between building energy conservation and building fire prevention. Due to the super hydrophobicity and extremely low density of silica aerogel, its powder is difficult to directly and evenly mix with other materials, and its interface compatibility with water-based systems is poor. Direct addition is easy to fly and float, which limits its performance, efficiency and convenience in the actual application of building materials.

[0003] Therefore, in order to make silica aerogel better used in building materials, it is urgent to solve the problem of interfacial compatibility between silica aerogel and aqueous system while retaining the structure and performance of silica aerogel. Silica aerogel powder can be dispersed in aqueous system by using dispersant to prepare silica aerogel dispersion slurry, but the static stability of slurry is often difficult to guarantee, and since air is easily mixed into slurry to produce a large number of bubbles, compounding with building materials to prepare products will cause problems such as uneven surface, paint film bubbles, pinhole defects, etc., which will affect product quality.

[0004] Therefore, there is a need for a stably dispersed and bubble-free silica aerogel slurry and a preparation method and application thereof. Summary of the invention

[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0006] On the one hand, the present application provides a silica aerogel slurry, which is prepared from the following materials, which are, by weight, 10-90 parts of water, 1-25 parts of hydrophobic silica aerogel powder, 0.01-3 parts of anionic surfactant, 0.01-0.9 parts of polymer electrolyte, 0.01-1 parts of suspending agent, 0.001-0.01 parts of pH regulator, 0.001-0.02 parts of defoaming agent and 0.001-0.01 parts of bactericide.

[0007] In one embodiment, the anionic surfactant can be selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, sodium alkyl polyoxyethylene ether carboxylate, sodium dodecyl sulfonate, sodium methylene bisnaphthalene sulfonate and sodium oleoyl methyl taurate. Optionally, the anionic surfactant is sodium dodecylbenzene sulfonate (SDBS).

[0008] In one embodiment, the polymer electrolyte may be selected from one or more of sodium polyacrylate, ammonium polyacrylate, polyacrylamide, sodium polystyrene sulfonate, polystyrene-maleic anhydride copolymer, and . Optionally, the polymer electrolyte is polyacrylamide (PAM).

[0009] In one embodiment, the polymer electrolyte has a number average molecular weight in the range of 500,000-3,000,000; alternatively, the polymer electrolyte has a number average molecular weight in the range of 2,000,000-3,000,000.

[0010] In one embodiment, the suspending agent can be one or more selected from hydroxypropyl methylcellulose, methylcellulose, hydroxyethylcellulose and carboxymethylcellulose. Optionally, the suspending agent is hydroxyethylcellulose (HEC).

[0011] In one embodiment, the hydrophobic silica aerogel powder has a particle size of 0.5 μm-500 μm and a bulk density of 60 kg / m 3 -90 kg / m 3 , thermal conductivity is 0.018W / m·k-0.021W / m·k and contact angle is 146°-149°.

[0012] In one embodiment, the water is distilled water or deionized water. Optionally, the water is deionized water.

[0013] In one embodiment, the pH adjuster may be selected from one or more of ammonia water, triethylamine, dimethylethanolamine, and 2-aminomethyl-1-propanol (AMP-95).

[0014] In one embodiment, the defoamer can be selected from one or more of BASF 2410 defoamer, Nopco 1375, Nopco 1370, Bek 024, and Digo 901 W. Optionally, the defoamer is a combination of Digo 901 W and BASF 2410 defoamer in a weight ratio of 1:1-5.

[0015] In one embodiment, the fungicide can be selected from one or more of methylisothiazolinone, N-octyl-4-isothiazolin-3-one, 4,5-dichloro-N-octyl-4-isothiazolin-3-one, 1,2-benzisothiazolin-3-one and n-butyl-1,2-isothiazolin-3-one. Optionally, the fungicide is 4,5-dichloro-N-octyl-4-isothiazolin-3-one (DCOIT).

[0016] In one embodiment, the pH of the silica aerogel slurry is in the range of 8.5-11.

[0017] In one embodiment, the silica aerogel slurry is prepared from the following materials, which are, by weight, 10-60 parts of water, 1-25 parts of hydrophobic silica aerogel powder, 0.1-0.3 parts of anionic surfactants, 0.2-0.6 parts of polymer electrolytes, 0.01-0.06 parts of suspending agents, 0.001-0.01 parts of pH regulators, 0.003-0.008 parts of defoaming agents, and 0.001-0.01 parts of bactericides.

[0018] On the other hand, the present application provides a method for preparing the above-mentioned silica aerogel slurry, comprising the following steps:

[0019] 1) Weigh each component;

[0020] 2) adding anionic surfactant, polymer electrolyte, suspending agent, defoaming agent and bactericide into water, and stirring at room temperature and pressure to obtain a uniformly mixed and stable composite dispersed solution;

[0021] 3) adding the hydrophobic silica aerogel powder to the composite dispersed solution, stirring until the hydrophobic silica aerogel powder is completely immersed in the composite dispersed solution, and adding a pH adjuster to adjust the pH value of the solution to 8.5-11 to obtain an initial slurry;

[0022] 4) The initial slurry is subjected to a vacuum degassing process to prepare the silica aerogel slurry.

[0023] In one embodiment, in step 2), the stirring speed may be 300-500 r / min, and the stirring time may be 5-15 minutes.

[0024] In one embodiment, in step 3), the stirring speed may be 1000-4500 r / min, and the stirring time may be 5-30 minutes.

[0025] In yet another aspect, the present application provides the use of the above-mentioned silica aerogel slurry in the preparation of thermal insulation coatings.

[0026] In one embodiment, the preparation method of the thermal insulation coating may include adding water, a defoamer, an antifreeze agent, and the above-mentioned bubble-free silica aerogel slurry into a container (such as a beaker) and stirring, then adding an elastic acrylic emulsion and a film-forming aid, and finally adding glass beads, a defoamer and a thickener to obtain a thermal insulation coating containing bubble-free silica aerogel.

[0027] The present application introduces a ternary composite system of a surfactant, a polymer electrolyte, and a suspending agent into an aqueous system, utilizes the synergistic steric hindrance of small molecules and macromolecules, and the hydrogen bonds between the suspension stabilizer and the water molecules form a high steric repulsion; the polymer ions and small molecule ions formed by the polymer electrolyte and the surfactant dissolving in water are adsorbed on the surface of the aerogel particles to form a double-thickness stable dispersion layer of charged ions; at the same time, by adjusting the pH value range of the slurry to the alkaline range, the absolute value of the Zeta potential of the slurry is further increased, and the Zeta potential with an absolute value of the surface potential of the aerogel particles greater than 20mV is achieved, and a strong electrostatic repulsion is formed between the particles, thereby ensuring the dispersion stability of the slurry.

[0028] The present application eliminates a large number of bubbles in the slurry through a composite process of defoaming agent and vacuum degassing, and the combined effects of strong electrostatic repulsion and high steric hindrance ensure the dispersion uniformity and stable durability of the aerogel slurry, so that the prepared aerogel slurry has excellent uniformity and stability and can be stored for a long time.

[0029] The present application adopts a combined process of a defoaming agent and a vacuum degassing process to synergistically degas the aerogel slurry, which significantly improves the problems of surface unevenness, paint film bubbles, pinhole defects, etc. of building materials products added with aerogel slurry, and reduces the impact of the slurry on the performance of aerogel-based building materials products.

[0030] The amount of additives used in the present application is small, which reduces the impact on the structure and performance of the aerogel, and the prepared aerogel slurry still maintains high hydrophobicity and low thermal conductivity after drying.

[0031] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0034] Figure 1 This is a photo of the appearance of the silica aerogel slurry prepared according to Example 1 of the present application;

[0035] Figure 2 is a photograph showing the contact angle of the aerogel slurry prepared in Example 3; and

[0036] Figure 3 This is a photograph of the appearance of a coating made from the silica aerogel slurry prepared according to Example 8 of the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0038] Unless otherwise specified, the materials used in the following examples and comparative examples are commercially available.

[0039] Example 1

[0040] This embodiment provides a method for preparing a silica aerogel slurry, comprising the following steps:

[0041] Weigh each component;

[0042] 0.1 parts by weight of sodium dodecylbenzene sulfonate SDBS, 0.2 parts by weight of polyacrylamide (PAM) having a number average molecular weight of 2,000,000, 0.01 parts by weight of hydroxyethyl cellulose HEC, 0.005 parts by weight of AMP-95, 0.004 parts by weight of a combination of 901W and 2410 defoamers (weight ratio of 1:3), and 0.002 parts by weight of DCOIT bactericide are added to 60 parts by weight of deionized water, and stirred at a speed of 500 r / min for 10 minutes in a high-speed disperser at normal temperature and pressure to obtain a uniformly mixed and stable composite dispersion solution;

[0043] 6 parts by weight of hydrophobic silica aerogel powder was added to the composite dispersion solution, and the mixture was stirred at a speed of 1000 r / min until the hydrophobic silica aerogel powder was completely immersed in the composite dispersion solution, and then stirred at a speed of 2500 r / min for 30 minutes, and 0.005 parts by weight of ammonia water was added to adjust the pH value of the slurry to 9.5 to obtain an initial slurry;

[0044] The initial slurry is subjected to a vacuum degassing process to prepare the silica aerogel slurry.

[0045] Figure 1 The figure shows the appearance of the silica aerogel slurry prepared in this example. Figure 1 It can be seen that the prepared aerogel slurry has good fluidity and still retains the structural characteristics of the aerogel.

[0046] Embodiment 2-7

[0047] The anionic surfactant, polymer electrolyte and suspending agent used in Examples 2-7 are the same as those in Example 1, and 60 parts by weight of deionized water and 6 parts by weight of silica aerogel powder are added. The difference lies in the different amounts of SDBS, PAM and HEC added.

[0048] After the silica aerogel slurry prepared in Examples 1-7 was dried at 60° C., thermal conductivity and contact angle tests were performed. The thermal conductivity was tested according to the national standard GB / T 10297-2015. The results are shown in Table 1 below.

[0049] Table 1 Thermal conductivity and contact angle of aerogel slurries prepared with different contents of SDBS, PAM and HEC.

[0050]

[0051] From the results in Table 1, it can be seen that the thermal conductivity of the aerogel slurry prepared by the ternary composite system mainly comprising a certain weight portion of SDBS, PAM and HEC is less than 0.021, and the contact angle is greater than 146°, which indicates that the aerogel slurry of the present application still maintains high hydrophobicity and low thermal conductivity after drying. Although not wishing to be bound by theory, it is believed that the synergy of the small molecule and the macromolecular substance in the ternary composite system of the present application and the hydrogen bonding of the suspension stabilizer and the water molecules increase the steric repulsion, thereby ensuring the stability of the aerogel slurry.

[0052] Figure 2 FIG. 3 is a photograph showing the contact angle of the aerogel slurry prepared in Example 3.

[0053] Comparative Examples 1-6

[0054] The preparation method of Comparative Examples 1-6 is the same as that of Example 1, but only includes aerogel slurry prepared by a single dispersion system or a binary composite system. The silica aerogel slurry prepared by Comparative Examples 1-6 was dried at 60° C. and then tested for thermal conductivity and contact angle. The thermal conductivity was tested according to the national standard GB / T 10297-2015. The results are shown in Table 2 below.

[0055] Table 2 Thermal conductivity and contact angle of aerogel slurries prepared by single dispersion system or binary composite system

[0056]

[0057] From the results in Table 2, it can be seen that compared with the slurry prepared by the ternary composite dispersion system of the present application, the aerogel slurry prepared by the single dispersion system or the binary composite system has a thermal conductivity greater than 0.025 W / m·k and a contact angle less than 137°, which means that the thermal conductivity is high and the contact angle is low. This may be because it is difficult to ensure the stability of the system with a single dispersion system or a binary composite system, and its addition amount needs to be increased, resulting in an increase in the thermal conductivity of the aerogel slurry and a decrease in the contact angle.

[0058] Embodiment 8-11

[0059] The anionic surfactant, polymer electrolyte and suspending agent used in Examples 8-11 are the same as those in Example 1, and the preparation process is the same. 60 parts by weight of deionized water and 6 parts by weight of silica aerogel powder are added. The difference lies in the type and number of defoamers. The silica aerogel slurry prepared in Examples 8-11 was dried at 60°C and then tested for thermal conductivity and contact angle. The thermal conductivity was tested according to the national standard GB / T 10297-2015, and the results are shown in Table 3 below. The aerogel slurry obtained in Examples 8-11 was prepared into an aerogel coating, coated on an asbestos-free fiber cement flat plate, placed under standard conditions for 24 hours, and the appearance of the coating was visually observed. The observation results are also shown in Table 3 below.

[0060] Table 3 Thermal conductivity / contact angle of aerogel slurries prepared with different defoamer types and fractions and the coating appearance of the corresponding coatings

[0061]

[0062] From the results in Table 3, it can be seen that the vacuum degassing and defoaming agent synergistic degassing process used in this application can improve the degassing quality of the aerogel slurry, thereby ensuring the uniform stability of the slurry; and because the amount of defoaming agent added is small, it has no effect on the thermal conductivity and contact angle of the aerogel slurry, and the aerogel slurry can still maintain low thermal conductivity and high hydrophobicity after drying. In addition, Figure 3 The following is a photograph showing the appearance of the coating made from the silica aerogel slurry prepared in Example 8. Figure 3 As shown, the aerogel coating prepared by using aerogel slurry with vacuum degassing and defoaming agent has a uniform and smooth coating surface, good leveling properties, and no bubbles or shrinkage holes.

[0063] Comparative Examples 7-10

[0064] The anionic surfactant, polymer electrolyte and suspending agent used in Comparative Examples 7-10 are the same as those in Example 1, and 60 parts by weight of deionized water and 6 parts by weight of silica aerogel powder are added. The difference lies in the different defoaming processes used, that is, only defoaming agent is used, or only vacuum defoaming is used. The thermal conductivity and contact angle of the aerogel slurry are tested, and the results are shown in Table 4; the prepared aerogel slurry is prepared into an aerogel coating, coated on an asbestos-free fiber cement flat plate, placed under standard conditions for 24 hours, and the appearance of the coating film is visually observed, and the observation results are also shown in Table 4.

[0065] Table 4 Thermal conductivity / contact angle of aerogel slurry prepared by different defoaming processes and defoamer contents and the coating appearance of the corresponding coatings

[0066]

[0067] From the results in Table 4, it can be seen that due to the large number of bubbles and the large amount of defoamer added, the aerogel slurry using only a defoamer for degassing has the problems of high thermal conductivity and low contact angle. At the same time, although the amount of defoamer added is increased (such as Comparative Example 9), some bubbles in the slurry are still not removed, which also leads to bubbles on the surface of the prepared coating film, affecting the flatness and uniformity of the coating film; although the aerogel slurry using the vacuum degassing process in Comparative Example 10 has low thermal conductivity and high hydrophobicity after drying test, there are still a small number of bubbles in the slurry that are not removed, and there are also a small number of bubbles on the surface of the prepared coating film. The above results show that since aerogel is light and porous, it is easy to introduce a large amount of air into the slurry when it is dispersed. It is difficult to completely remove the bubbles in the aerogel slurry using a single defoaming process, that is, only using a defoamer or only using a vacuum degassing method.

[0068] Examples 12-15

[0069] The anionic surfactant, polymer electrolyte and suspending agent used in Examples 12-15 are the same as those in Example 1, the preparation process is the same, and 60 parts by weight of deionized water and 6 parts by weight of silica aerogel powder are added. The difference is that the pH value of the aerogel slurry is different; the prepared aerogel slurry is subjected to a Zeta potential test, and the results are shown in Table 5; the prepared aerogel slurry is prepared into an aerogel coating, coated on an asbestos-free fiber cement flat plate, placed under standard conditions for 24 hours, and the appearance of the coating film is visually observed. The observation results are also shown in Table 5.

[0070] Table 5 Zeta potential absolute values ​​of aerogel slurries with different pH values ​​and the coating appearance of the corresponding coatings

[0071] Serial number Slurry pH Zeta potential absolute value / mv Coating appearance Example 12 8.8 23.1 The coating is uniform, without bubbles or shrinkage cavities Example 13 9.5 25.4 The coating is uniform, without bubbles or shrinkage cavities Embodiment 14 10.2 24.2 The coating is uniform, without bubbles or shrinkage cavities Embodiment 15 10.6 23.5 The coating is uniform, without bubbles or shrinkage cavities

[0072] From the results in Table 5, it can be seen that the absolute value of the Zeta potential of the aerogel slurry prepared in the alkaline range (such as 8.8-10.6) pH value is greater than 20mV, and has no effect on the prepared aerogel coating film, the coating surface is uniform and smooth, the leveling is good, and no bubbles or shrinkage holes are generated. Although it is not desired to be bound by theory, it is believed that the polymer ions and small molecule ions in the ternary composite system of the present application are adsorbed on the surface of the aerogel particles to form a double-thickness stable dispersion layer of charged ions, and the pH value in the alkaline range further increases the absolute value of the Zeta potential of the slurry, significantly enhancing the electrostatic repulsion between the particles, thereby ensuring the dispersion stability of the aerogel slurry.

[0073] Examples 16-18

[0074] The anionic surfactant, polymer electrolyte and suspending agent used in Examples 16-18 are the same as those in Example 1, the preparation process is the same, and 60 parts by weight of deionized water and 6 parts by weight of silica aerogel powder are added. The difference is that the number average molecular weight of the polymer electrolyte PAM is different. The prepared aerogel slurry is subjected to Zeta potential test, and the results are shown in Table 6; the prepared aerogel slurry is prepared into an aerogel coating, coated on an asbestos-free fiber cement flat plate, left under standard conditions for 24 hours, and the appearance of the coating film is visually observed. The observation results are also shown in Table 6.

[0075] Table 6 Zeta potential absolute values ​​of aerogel slurries with different molecular weights of PAM and the coating appearance of the corresponding coatings

[0076] Serial number Molecular weight of PAM Zeta potential absolute value / mv Coating appearance Example 16 2000000 24.1 The coating is uniform, without bubbles or shrinkage cavities Embodiment 17 2500000 24.4 The coating is uniform, without bubbles or shrinkage cavities Embodiment 18 3000000 25.0 The coating is uniform, without bubbles or shrinkage cavities

[0077] From the results in Table 6, it can be seen that the absolute value of the Zeta potential of the aerogel slurry prepared by the ternary composite system containing the polymer electrolyte PAM with a number average molecular weight in a range (such as 2000000-3000000) is greater than 20mV, and the surface of the prepared aerogel coating film is uniform and flat, with good leveling, and no bubbles or shrinkage holes are generated. Although it is not desired to be bound by theory, it is believed that the polymer ions generated by the polymer electrolyte with a certain molecular weight dissolved in water in the ternary composite system of the present application are adsorbed on the surface of the aerogel particles, which increases the charge density of the ion edge surface, increases the absolute value of the particle surface potential, and increases the electrostatic repulsion. At the same time, the long chain of the polymer electrolyte is fully extended in the medium to form a high steric barrier layer to prevent the agglomeration of ions, thereby ensuring the dispersion stability of the aerogel slurry.

[0078] Further, regarding the long-term static stability of the aerogel slurry, the aerogel slurries prepared in Examples 1-18 and Comparative Examples 1-6 were tested. The slurries prepared in Examples 1-18 and Comparative Examples 1-6 were placed in a constant temperature and humidity environment at a temperature of 25±2°C and a relative humidity of 40-50%, and left to stand for 180 days to test whether there was sedimentation, stratification, or water seepage. The results are shown in Table 7.

[0079] Table 7 Static stability test results of aerogel slurry

[0080]

[0081] From the results in Table 7, it can be seen that the aerogel slurry containing the ternary composite system in the embodiment of the present application has excellent uniform stability, and will not settle, stratify, or ooze after standing for a long time. The slurry still maintains high hydrophobicity and low thermal conductivity after drying, and can be stored for a long time. The defoaming agent and vacuum degassing process are used to synergistically degas the aerogel slurry, which improves the problems of surface unevenness, paint film bubbles, pinhole defects, etc. of the building materials added with aerogel slurry, and reduces the impact of the slurry on the performance of aerogel-based building materials. On the contrary, the aerogel slurry of the comparative example that does not contain the ternary composite system will experience severe sedimentation, stratification, and oozing after standing for a long time.

[0082] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Those skilled in the art can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A silica aerogel slurry, characterized in that: The silica aerogel slurry is prepared from the following materials, which are, by weight, 10-90 parts of water, 1-25 parts of hydrophobic silica aerogel powder, 0.01-3 parts of anionic surfactant, 0.01-0.9 parts of polymer electrolyte, 0.01-1 parts of suspending agent, 0.001-0.01 parts of pH regulator, 0.001-0.02 parts of defoaming agent and 0.001-0.01 parts of bactericide.

2. The silica aerogel slurry according to claim 1, characterized in that: The anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, sodium alkyl polyoxyethylene ether carboxylate, sodium dodecyl sulfonate, sodium methylene bisnaphthalene sulfonate and sodium oleoyl methyl taurate; and / or, The suspending agent is selected from one or more of hydroxypropyl methylcellulose ether, methylcellulose, hydroxyethylcellulose and carboxymethylcellulose.

3. The silica aerogel slurry according to claim 1, characterized in that: The polymer electrolyte is selected from one or more of sodium polyacrylate, ammonium polyacrylate, polyacrylamide, sodium polystyrene sulfonate and polystyrene-maleic anhydride copolymer.

4. The silica aerogel slurry according to claim 3, characterized in that: The polymer electrolyte has a number average molecular weight in the range of 500,000-3,000,000; optionally, the polymer electrolyte has a number average molecular weight in the range of 2,000,000-3,000,000.

5. The silica aerogel slurry according to claim 1, characterized in that: The defoamer is selected from one or more of BASF 2410 defoamer, Nopco 1375, Nopco 1370, Bek 024 and Digo 901W; optionally, the defoamer is a combination of Digo 901W and BASF 2410 defoamer in a weight ratio of 1:1-5.

6. The silica aerogel slurry according to any one of claims 1 to 5, characterized in that: The hydrophobic silica aerogel powder has a particle size of 0.5 μm-500 μm and a bulk density of 60 kg / m 3 -90 kg / m 3 , thermal conductivity is 0.018W / m·k-0.021W / m·k and contact angle is 146°-149°.

7. The silica aerogel slurry according to any one of claims 1 to 5, characterized in that: The fungicide is selected from one or more of methylisothiazolinone, N-octyl-4-isothiazolin-3-one, 4,5-dichloro-N-octyl-4-isothiazolin-3-one, 1,2-benzisothiazolin-3-one and n-butyl-1,2-isothiazolin-3-one.

8. The silica aerogel slurry according to any one of claims 1 to 5, characterized in that: The water is distilled water or deionized water; and / or The pH regulator is selected from one or more of ammonia water, triethylamine, dimethylethanolamine, and 2-aminomethyl-1-propanol; Optionally, the pH of the silica aerogel slurry is in the range of 8.5-11.

9. A method for preparing a silica aerogel slurry according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: 1) Weigh each component; 2) adding anionic surfactant, polymer electrolyte, suspending agent, defoaming agent and bactericide into water, and stirring at room temperature and pressure to obtain a uniformly mixed and stable composite dispersed solution; 3) adding the hydrophobic silica aerogel powder to the composite dispersed solution, stirring until the hydrophobic silica aerogel powder is completely immersed in the composite dispersed solution, and adding a pH adjuster to adjust the pH value of the solution to 8.5-11 to obtain an initial slurry; 4) The initial slurry is subjected to a vacuum degassing process to prepare the silica aerogel slurry.

10. Use of the silica aerogel slurry according to any one of claims 1 to 8 in preparing thermal insulation coatings.